What happens when the newborn hearing screening program is integrated with congenital Cytomegalovirus infection screening? Preliminary results in a tertiary hospital. (27th May 2021) - Palma, Silvia; Botti, Cecilia; Roversi, Maria Federica; Bettini, Margherita; Pietrosemoli, Paola; Berardi, Alberto; Genovese, Elisabetta
Abstract: Objective: Early diagnosis of congenital Cytomegalovirus (cCMV) infection related hearing loss has increased since the spread of newborn hearing screening (NHS) programs worldwide. However, since most newborns affected are asymptomatic at birth but may develop hearing loss later, some of them may elude the NHS. The aim of this study was to compare the results in two cohorts of children, in one of which all newborns who failed the NHS were tested for cCMV. Methods: We retrospectively compared the results of early diagnosis of cCMV-related hearing loss between two groups of patients at a high-volume centre. Group 1 included the first 3 years of activity without a targeted cCMV screening and was composed of children born between 2012 and 2014. Group 2 included neonates born between 2015 and 2017: in this group, those who failed the NHS underwent urine CMV analysis within 14 days. Results: There were 17, 229 live births during the study period, 20 were diagnosed with cCMV infection, with a global prevalence of 1.1:1000. 72 neonates (0.42%) with hearing loss were identified, 7% of which were diagnosed with cCMV infection, 3/34 (8.8%) in group 1 and 2/38 (5.3%) in group 2 ( p  = .66). One newborn in group 2 was identified through the protocol. The percentage of patients affected by cCMV-related hearing loss diagnosed during the NHS showed non-significant differences in the two groups. Conclusion: Our results suggest that the suspicion index of cCMV infection in a tertiary hospital is currently high and neonatologists are able to identify most symptomatic cases which have higher risk of developing hearing loss. Coupling the cCMV screening and the NHS program is worthwhile as it allows early recognition of asymptomatic cases with hearing loss and subsequent immediate administration of antiviral therapy.